Parental Differences in Knowledge, Perception, and Safety Behaviors Regarding Home Injuries in an Urban Malaysian District - Mohd Basar, Munirah; Ali, Mohd Fairuz; Abdul Aziz, Aznida (UI Scholars Hub, 2021)
Background: Parents play an essential role in the prevention of home-related injuries among children. Traditionally, mothers provided direct overall care, whereas evidence on fathers' roles in children’s injuries is limited. This study assesses the differences between parents of children attending kindergarten regarding their knowledge and perception of home injuries and safety behaviors. Methods: A cross-sectional study was conducted from January to April 2018 in 10 private kindergartens in the Selangor district in Malaysia. Self-administered questionnaires on sociodemographic data, knowledge of home injuries, perceptions toward home injuries, and safety behaviors at home were distributed. Descriptive and bivariate analyses were done to determine associated factors. Results: A total of 147 fathers and 182 mothers participated. Differences in parental knowledge, perception, and safety behaviors were not statistically significant (p > 0.05). A poor correlation existed between both knowledge (r = 0.099, p = 0.073) and perception (r = 0.207, p < 0.001) with behavior scores. Most parents regarded injuries involving children at home as unavoidable and perceived mild injuries as the norm. However, most parents agreed that monitoring children’s activities could reduce injury risk. Conclusions: Healthcare practitioners should promote safe behavioral practices to both parents equally to improve their children's knowledge and perception of home injuries.